A study of acquisition premiums of Singapore's listed companies. - Lim, Chin Chong. (2009)
Acquisitions have played an important part in the growth of several publicly listed companies in Singapore. In acquisitions, the acquiring company typically pays a premium to the shareholders of the target companies. Various studies have documented a wide range of acquisition premiums offered in the securities markets around the world including the Stock Exchange of Singapore. As the magnitude of the premium is significant to the success of the acquisition plan, a comprehensive study of the premium-setting aspect is warranted.